2011
DOI: 10.33141/po.2011.78.13
|View full text |Cite
|
Sign up to set email alerts
|

Ocena znaczenia finansowych instrumentów wspierania, stosowanych w Polsce i innych krajach Unii Europejskiej

Abstract: W artykule zaprezentowano ocenę znaczenia finansowych instrumentów wspierania dla małych i średnich przedsiębiorstw (MŚP). Przedstawiono metodologię prowadzonych badań, scharakteryzowano ankietowane przedsiębiorstwa oraz przeanalizowano otrzymane wyniki. Na tej podstawie opracowano wnioski dotyczące znaczenia poszczególnych instrumentów pomocy dla MŚP. (abstrakt oryginalny)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In connection to the above, a Polish entrepreneur has to make about 40 payments at constitute 40% of his profits and takes approximately 420 hours per year (Woźniak, 2012). Nevertheless, the survey made by Woźniak (2011) revealed that SMEs find fiscal incentives as very important for their development. Moreover, most of them regard tax breaks for investments as justified (Zbroińska, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In connection to the above, a Polish entrepreneur has to make about 40 payments at constitute 40% of his profits and takes approximately 420 hours per year (Woźniak, 2012). Nevertheless, the survey made by Woźniak (2011) revealed that SMEs find fiscal incentives as very important for their development. Moreover, most of them regard tax breaks for investments as justified (Zbroińska, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organic cosmetics is a product category that has been growing rapidly, both globally and in Europe. Increased consumer interest in this product category is related to, among other factors, concern for the environment, widespread promotion of the concept of sustainable development, and interest in innovation in the cosmetics market (Klimczyk-Bryk 2000, Witek 2015, Nagarajan et al 2022.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%